The evolution of Kariat Arekmane Coast (province of Nador-Morocco) diachronic study and evaluation of proposed solutions - Elallati Samia; Ben harra Abdessalam; Bouhadi Amine; Falouss Safae; Issa Lamiae Khali; Raissouni Ahmed; El arrim Abdlekrim (E3S Web of Conferences, 2024)
The coastline of the Nador region, in particular at Kariat Arekmane, is undergoing rapid changes influenced by natural and human factors, including submersion and erosion. An analysis of the coastline in this area has been performed in order to better understand these changes. The study began with a granulometric analysis, followed by a diachronic analysis of the coastline using the DSAS method in a GIS-ARCGIS environment. The results reveal significant variations in the study area, alternating between accretion and erosion. On average, the annual erosion rate is 0.66 m/year, while the accretion rate is 0.21 m/year. The average coastal change at Kariat Arekmane is 1.102 m/year, divided into two sectors: the first, undergoing severe erosion, comprises sandy shores and cliff areas, while the second, the western beach, benefits from accretion due to protective rock structures. The main causes of these coastal changes are coastal infrastructures and hydrodynamic forces. To solve this problem, several solutions for preserving Arekmane's coastline are currently being proposed and evaluated. Appropriate coastal management is essential to protect this region and mitigate the adverse effects of coastal erosion.